Using Content Coding and Automatic Item Generation to Improve Test Security - Gierl, Mark J.; Shin, Jinnie; Firoozi, Tahereh; Lai, Hollis (Frontiers in Education, 2022)
Automatic item generation (AIG) is the process of using models to generate items using computer technology. AIG is a scalable content development method because it relies on the item model as the unit of analysis which means that it is more efficient and economical compared to traditional item development. But to use the generated items effectively, they must be managed properly. Managing a bank that could include millions of items results in problems related to identifying, organizing, and securing the content. As a result, the challenges inherent to managing item models and generated items warrant a shift in banking methodology where the management task must be accomplished using content coding at the model level. The purpose of our paper is to describe and illustrate methods that use content coding to organize and secure generated items in a bank.